Preparation of some non-homogeneous cyclic compounds (pyrazolines and Isooxazolins) - Nem Salim (College of Education for Pure Sciences, 2012)
Abstract In this paper number of some dichalcones (1-6) were prepared by reaction of one mole of acetone with two moles of benzaldehyde and benzaldehydes substituted (2-methoxy, 4-methoxy, 3,4-dimethoxy, 2-chloro and 4-nitro) in the presence of (10%) sodium hydroxide as a base. Pyrazolenes (7-12) were prepared from the reaction of dichalcones (1-6) with acetic hydrazide in the presence of (45%) sodium hydroxide as a base. Isooxazoline (13-18) were prepared from the reaction of dichalcones (1-6) with hydroxyl amine hydrochloride in the presence of (10%) sodium hydroxide as a base. These compound were studied and identified by physical and spectral methods.